Analysis of cholesterol and triglyceride levels in obese patients - Pratiwi, Chalies Diah; Puspitasari, Eka; Hermawati, Andyanita Hanif (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2023)
Obesity is excessive fat accumulation in the body. Continuous obesity and excessive food intake can cause metabolic system disorders in the form of hypercholesterolemia. Analysis of cholesterol and triglyceride levels in obese patients needs to be carried out to assist them in making healthier lifestyle changes. This study aims to analyze cholesterol and triglyceride levels in obese patients. The research method used is experimental with a laboratory approach. The samples to be analyzed were 20 obese people obtained by purposive sampling technique in the Tulungagung area. The research instruments used were height and weight check sheets and cholesterol and triglyceride test results sheets. Research data analysis technique by examining cholesterol and triglyceride levels using a MicroLab C-300 spectrophotometer and will be analyzed descriptively quantitatively. The results showed that 15 patients had normal cholesterol levels (75%) with criteria <200 mg/dl and 5 patients had high cholesterol levels (25%) with criteria >200 mg/dl, while there were 17 patients with normal triglyceride levels (85 %) with criteria <150 mg/dl and 3 patients had high triglyceride levels (15%) with criteria >150 mg/dl. The conclusion of this study is that people who are obese do not necessarily have high cholesterol and triglyceride levels. However, when a person weighs > 80 kg, it is recommended to start paying attention to a healthier lifestyle.